Properties Of Soy Protein Isolate-chitosan Bioadhesives For Production Of Oil Palm Trunk Particleboard - Lamaming, Sofie Zarina (2023)
Formaldehyde-based adhesive had been used commercially in production of wood-based composite. However, since it contains carcinogenic formaldehyde that is hazardous mainly to human health, researchers all over the globe are focusing on producing formaldehyde-free adhesive from natural resources. Soy protein had been used to produce adhesive since the early years due to its good properties such as fast growth, biocompatibility, and environmentally friendly. In this study, bioadhesive from soy protein isolate with addition of chitosan were produced then mixed with oil palm trunk to make particleboard with the aim to improve the properties of the particleboard especially its dimensional stability. The particleboard with targeted density of 0.80 g/mm3 and 10% adhesive content (based on oven dry weight of oil palm trunk) were produced by mixing the oil palm trunk particles with different ratio soy protein isolate and chitosan (3:1, 2:1, 1:1, 1:2 and 1:3) before pressed with hot press machine at 180°C and 5 MPa pressure for 8 minutes. The properties of adhesives made such as its viscosity and solid content were evaluated and compared with each other. The chemical analysis of oil palm trunk including its extractives, holocellulose, alpha cellulose and lignin content were assessed to determine its effect on the mechanical strength of particleboard produced. The particleboards bonded with soy protein isolate and chitosan adhesives produced were tested for its physical, mechanical and thermal properties as well as its morphological images and compared with the particleboards bonded with commercial urea formaldehyde adhesive